Detection of Japanese encephalitis virus in wild boars and comparison of blood profiles between wild boars and domestic pigs in Selangor - Tan, Wei Cheit; Hamzah, Hazilawati; Ooi, Peck Toung; Allaudin, Zeenathul Nazariah; Kumar Sharma, Reuben Sunil; Ho, G. C.; Lee, C. L. (2012)
The Japanese encephalitis virus (JEV) RNA has been detected in the vector (mosquitoes) collected in Selangor almost two decades ago, whilst the JEV status of the potential reservoir (wild boars) in Selangor is yet not being investigated. Blood profiles can be used for health monitoring, however the study on wild boar’s blood profile was limited. This study was performed to detect the JEV RNA in wild boars in Selangor and to determine the haematological and serum biochemical values of the wild boars; blood profiles of domestic pigs were also determined for comparison. The JEV RNA (genotype I and/or III) was detected in one of 21 (4.8%) tonsils. The WBC count, segmented neutrophil count and globulin concentration of the wild boars were significantly lower than the domestic pigs whilst serum AST and CK of the wild boars were significantly higher than the domestic pigs.